Influence of gender, working field and psychosocial factors on the vulnerability for burnout in mental hospital staff: results of an Austrian cross‐sectional study. Issue 1 (14th August 2017) - Schadenhofer, Petra; Kundi, Michael; Abrahamian, Heidemarie; Stummer, Harald; Kautzky‐Willer, Alexandra
Abstract : Introduction: According to the European Agency for Safety and Health at Work (EU‐OSHA), hospitals represent a work environment with high job strain. Prolonged perceived occupational stress may result in symptoms of burnout, such as emotional exhaustion (EE), depersonalisation (DP) and reduced personal accomplishment (PA). Understanding which factors may reduce vulnerability for burnout is an important requirement for well‐targeted occupational stress prevention in mental hospital staff. Objective: To identify the influence of gender, age, working field, family structure, education, voluntarily occupational training during holidays and length of stay on job on occupational stress perception. Methods: In a cross‐sectional design, 491 employees (311 female, 180 male) of an Austrian mental health centre participated in the study. The extent of perceived occupational stress was assessed by the Maslach Burnout Inventory (MBI) with the scales for emotional exhaustion, depersonalisation and personal accomplishment. Participants were divided according to their working field in those working with/without patients. Findings: Prevalence of emotional exhaustion was higher in women working with patients compared to men working with patients (25% vs. 18%, p = 0.003). Age above 45 years was significantly associated with decreased vulnerability for burnout in men (EE p = 0.040, DP p = 0.010, PA p = 0.007), but not in women. A lower level of education had a significant impact on depersonalisation in both sexes (p = 0.001 for men, p = 0.048 for women). Length of stay on job showed a significant influence on emotional exhaustion. No significant relationship was found between family structure and vulnerability for burnout. Conclusion: Gender had a differential effect on perceived occupational stress indicating a need for gender‐tailored preventive strategies. Age, working field, education, voluntarily occupational training during holidays and length of stay on job affect vulnerability for burnout in mental hospital staff.